A comprehensive investigation on CVD growth thermokinetics of h-BN white graphene. (1st August 2016) - Song, Xiufeng; Li, Qiguang; Ji, Jianping; Yan, Zhong; Gu, Yu; Huo, Chengxue; Zou, Yousheng; Zhi, Chunyi; Zeng, Haibo
Abstract: As an isomorph of graphene, monolayer hexagonal boron nitride (h-BN), so-called white graphene, has been in the spotlight of two-dimensional materials due to its outstanding properties. However, the growth of large and uniform white graphene monocrystalline with low density of defects is still a great challenge. Here, we present a comprehensive investigation on the growth thermokinetics of white graphene monocrystalline domains via atmospheric pressure chemical vapor deposition with the solid ammonia borane as precursors, which will be more suitable for future industrial production due to the handy process and precursor. The single domain size, coverage on substrate, and thickness of white graphene were taken as targeted parameters of products. And then, their dependences on the flow rate of carrier gas, heating temperature of ammonia borane, growth temperature and time were studied in details. Finally, after optimizing the above conditions, both white graphene monocrystalline domains as large as 80 μ m 2 and polycrystalline ultrathin film with coverage ratio of 95%–100% can be achieved facilely without using vacuum technique. Such white graphene products would be of great significance for the tunnel barrier for the tunneling transistor and the dielectric layers for nanocapacitor with the graphene based heterostructures.